Discriminação auditiva-visual em deficientes auditivos pós-linguais com implante coclear - PEREIRA, Fabiane da Silva (Universidade Federal do Pará, 2018)
Aiming the evaluation of listener-behavior training on speaker-behavior, specifi cally if individuals with hearing impairment and cochlear implant would: (a) learn audio-visual conditional discriminations with conventional and non-conventional words; (b) form stimulus classes; (c) present generalized responses to other audio frequencies; and (d) transfer the acquired hearing competences to speaker repertoires, two adults with post-lingual hearing loss and cochlear implant were exposed to a seven phases’ matching to sample conditional discriminations teaching program consisting of: 1) Pre-training of auditory-visual tasks using fading out; 2) Pre-test of naming to evaluate the speaker behavior, 3) Teaching relations between dictated words and fi gures; 4) Teaching relations between dictated and written words, 5) Test of class formation; 6) Test of hearing generalization; 7) Post-test of naming. The participants learned the directly taught relations, demonstrated class formation and generalization. Comparing pre- and post-tests, they showed higher correspondence between their speaker behavior and verbal community’s speaker behavior. The possibilities of this methodology for speaking rehabilitation in this population is discussed.